Exploring L2 learners' Task-related Identities in a Reading Circle Task Through Conversation Analysis - Le, Hoa T. V. (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2021)
Using conversation analysis as the research approach, this study explores how L2 learners utilize their task-related identities during task interactions and how those identities are used as resources for task management. Eight students in an ESL academic reading class formed two groups while they did their reading circle task for six rounds. In each round, the students took turns to be in charge of a specific role in the discussion session (i.e., discussion leader, notetaker, vocabulary definer, and contextualizer). Data was collected from all rounds and analyzed for emerging patterns. Results showed that (a) the participants used each other’s assigned identities skillfully to orient the group to the institutional goal, and (b) the participants used their own existing obligations to problematize the task interactions. By providing insights on those dynamic task-related identities, this study broadens our understanding of interactions happening at the task implementation stage and suggests pedagogical implications.